Disciplining Student Activism: Secondary Schools as Sites of Resistance and Control in Hong Kong. Issue 4 (24th August 2021) - Tong, Kin‐long; Yuen, Samson
Abstract : Throughout history, student activism has been a powerful force in promoting social and political changes. During the process, schools—serving in part as an institution of social control—often become a site of contestation, where student activists may clash with the school authorities when mobilizing their peers and fighting for protest goals. Focusing on Hong Kong's Anti‐Extradition Bill Movement, which saw extensive participation among secondary school students, this article examines how secondary schools in a non‐democratic context dealt with campus protests and how student activists negotiated space for dissent. Based on an on‐site survey on student protesters and semi‐structured interviews with teachers and student activists, we demonstrate how schools attempted to de‐politicize the campus through spontaneously expanding their "hidden curriculum, " particularly by creating and repurposing school rules in the face of mounting student activism. In turn, progressive teachers and students developed innovative tactics to negotiate or circumvent these ad hoc school rules. Our findings contribute to the field of sociology of education and contentious politics by exploring the politics of school rules and the complex relationship between schools, teachers, and students during social movements.